Role of Small RNAs in Regulating Virulence Gene Expression in Salmonella Typhimurium and Pseudomonas aeruginosa: A Comparative Review - Mehboob, Abdul Ahad; Shakeel, Faiqa; Sajjad, Hasnain; Munir, Anam; Tabassum, Faiqa; Fatima, Urooj (Indus Journal of Bioscience Research, 2025)
In Gram-negative pathogens, small RNAs (sRNAs) play a crucial role as post-transcriptional regulators, coordinating the expression of virulence genes essential to pathogenesis. The function of sRNAs in Salmonella Typhimurium and Pseudomonas aeruginosa, model organisms for bacterial virulence research because of their unique ecological niches and intricate pathogenicity, is examined in this review. sRNAs govern quorum sensing, biofilm formation, and antibiotic resistance in Pseudomonas and Type III Secretion Systems (T3SS), motility, and stress responses in Salmonella. We highlight the function of RNA chaperones such as Hfq by comparing common and distinct sRNA-mediated regulatory mechanisms. RNA-seq and CRISPRi are two experimental methods that have improved the discovery and functional characterization of sRNA. With the potential to create synthetic sRNA mimics, antisense oligonucleotides, and vaccines, sRNAs provide new antivirulence targets for therapeutic use. Regulatory redundancy and context-dependent expression are obstacles that call for integrative multi-omics and systems biology methodologies. This review provides information on the therapeutic and biotechnological potential of sRNAs in the fight against infections by highlighting them as important regulators of bacterial pathogenesis.